Suppression of influenza virus infection by the orf virus isolated in Taiwan - LIN, Fong-Yuan (J Vet Med Sci, 2015)
Orf virus (ORFV), a member of parapoxvirus, is an enveloped virus with genome of double-stranded DNA. ORFV causes contagious pustular dermatitis or contagious ecthyma in sheep and goats worldwide. In general, detection of viral DNA and observing ORFV virion in tissues of afflicted animals are two methods commonly used for diagnosis of orf infection; however, isolation of the ORFV in cell culture using virus-containing tissue as inoculum is known to be difficult. In this work, the ORFV (Hoping strain) isolated in central Taiwan was successfully grown in cell culture. We further examined the biochemical characteristic of our isolate, including viral genotyping, viral mRNA and protein expression. By electron microscopy, one unique form of viral particle from ORFV infected cellular lysate was demonstrated in the negative-stained field. Moreover, immunomodulating and anti-influenza virus properties of this ORFV were investigated. ORFV stimulated human monocytes (THP-1) secreting proinflammatory cytokines IL-8 and TNF-α. And, pre-treatment of ORFV-infected cell medium prevents A549 cells from subsequent type A influenza virus (IAV) infection. Similarly, mice infected with ORFV via both intramuscular and subcutaneous routes at two days prior to IAV infection significantly decreased the replication of IAV. In summary, the results of a current study indicated our Hoping strain harbors the immune modulator property; with such a bio-adjuvanticity, we further proved that pre-exposure of ORFV protects animals from subsequent IAV infection.